An Attitude in Appraisal Analysis of Interrogator–Suspect Interaction in Indonesia - Ramadani Ramadani; Amin Basri; Prima Yanti Siregar; Heridayani Heridayani; Nurima Rizki Dongoran; Asri Sanusi (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aimed to analyse the interpersonal strategies in appraisal system particularly in attitude used by interrogator and suspects during police interrogations in Indonesia. This research employed a qualitative approach with a case study design. Data consisted of interrogation exchanges between interrogator and five theft suspects, collected through recording, observation, and note-taking techniques. Data analysis was conducted using appraisal theory within a Systemic Functional Linguistics (SFL) framework, focusing on the attitude categories (affect, assessment, and appreciation). The results indicate that the affect (feeling) category was the most dominant, primarily used by suspects to express their emotional states. Meanwhile, interrogator predominantly used appraisal (assessment) to shape the suspects' behaviour. These findings suggest a strong power relationship in the interrogation interaction, with interrogator acting as the controlling and enabling party, while the suspects were emotionally distressed. Abstrak Penelitian ini bertujuan untuk menganalisis strategi interpersonal dalam sistem penilaian, khususnya sikap yang digunakan oleh penyidik dan tersangka selama interogasi polisi di Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data terdiri dari pertukaran interogasi antara penyidik dan lima tersangka pencurian, yang dikumpulkan melalui teknik perekaman, observasi, dan pencatatan. Analisis data dilakukan menggunakan teori penilaian dalam kerangka Linguistik Fungsional Sistemik (SFL), dengan fokus pada kategori sikap (afek, penilaian, dan apresiasi). Hasil menunjukkan bahwa kategori afek (perasaan) adalah yang paling dominan, terutama digunakan oleh tersangka untuk mengekspresikan keadaan emosional mereka. Sementara itu, penyidik sebagian besar menggunakan penilaian (assessment) untuk membentuk perilaku tersangka. Temuan ini menunjukkan hubungan kekuasaan yang kuat dalam interaksi interogasi, dengan penyidik bertindak sebagai pihak pengendali dan pendukung, sementara tersangka mengalami tekanan emosional.